2022
DOI: 10.3389/fonc.2022.973810
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for comparing the efficacy of left-open single-flap technique versus double-flap technique after proximal gastrectomy: A multicenter randomized controlled trial

Abstract: BackgroundProximal gastrectomy has gradually gained more attention due to its superiority in retaining the function of part of the stomach. The inevitable loss of the antireflux barrier and postoperative complications resulting from proximal gastrectomy can severely affect the quality of life. Continuous improvements in digestive tract reconstruction after proximal gastrectomy have yielded the development of a variety of methods with antireflux functions. Recently, our center attempted the left-open single-fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Wang et al reported the short-term efficacy of laparoscopic PG and esophagogastrostomy with single-flap technology in seven patients, observing satisfactory short-term efficacy for laparoscopic PG with single-flap anastomosis [49]. Yang et al [50] proposed single-flap anastomosis on the basis of double-flap anastomosis, that is, a "⊐"-shaped single flap with an opening toward the small curved side was made on the front wall of the gastric stump, the entire layer of the front wall of the gastric stump was cut at the lower edge of the muscle flap transversely, mucosal-esophageal anastomosis of the anterior wall of the stomach was performed, and the single flap and anterior wall of the stomach were continuously sutured before the anastomosis. A multicenter, prospective, randomized controlled study with a target completion date of July 31, 2027 could provide better conclusions from the research results.…”
Section: Single-flap Anastomosismentioning
confidence: 99%
“…Wang et al reported the short-term efficacy of laparoscopic PG and esophagogastrostomy with single-flap technology in seven patients, observing satisfactory short-term efficacy for laparoscopic PG with single-flap anastomosis [49]. Yang et al [50] proposed single-flap anastomosis on the basis of double-flap anastomosis, that is, a "⊐"-shaped single flap with an opening toward the small curved side was made on the front wall of the gastric stump, the entire layer of the front wall of the gastric stump was cut at the lower edge of the muscle flap transversely, mucosal-esophageal anastomosis of the anterior wall of the stomach was performed, and the single flap and anterior wall of the stomach were continuously sutured before the anastomosis. A multicenter, prospective, randomized controlled study with a target completion date of July 31, 2027 could provide better conclusions from the research results.…”
Section: Single-flap Anastomosismentioning
confidence: 99%